Integrating Skill Development and Water Confidence in Freestyle Swimming: An Application-Based Training Model - Rossa Linda Ardiningsih; Akhmad Sobarna; Sumbara Hambali (Jurnal Porkes, 2026)
This study aimed to develop and evaluate an application-based training model that integrates technical skill development and water confidence in freestyle swimming. A research and development approach was employed using the ADDIE framework, encompassing analysis, design, development, implementation, and evaluation stages. The developed model was implemented through a mobile application featuring progressive freestyle swimming drills, visual demonstrations, and confidence-oriented learning activities. Participants consisted of 20 freestyle swimmers selected through simple random sampling. Model validity was examined through expert review using Aiken’s V coefficient, while practicality was assessed based on responses from coaches and swimmers. Effectiveness was evaluated using a pretest–posttest design and analyzed with nonparametric statistics. The results indicated high content validity and practicality of the training model. Significant improvements were observed in overall freestyle swimming skills following implementation, with notable gains in breathing coordination, arm-leg coordination, and movement efficiency. Improvements in observable confidence-related behaviors, such as more relaxed breathing patterns and stable body alignment, were also identified. These findings suggest that integrating skill-oriented drills with confidence-enhancing strategies within an application-based framework can effectively support motor learning in aquatic environments. In conclusion, the proposed training model offers a theoretically grounded and practically feasible approach to improving freestyle swimming skills and water confidence. The integration of digital technology, motor learning principles, and confidence-oriented pedagogy provides a valuable contribution to swimming education and coaching practice.